Discordant Responses to MAPK Pathway Stimulation Include Axonal Growths in Adult Drosophila Photoreceptors - Mecklenburg, Kirk L.; Weghorst, Forrest P.; Freed, Stephanie A.; O’Tousa, Joseph E. (Frontiers in Molecular Neuroscience, 2018)
Wallenda (WND) is the Drosophila member of a conserved family of dual leucine kinases (DLK) active in both neuronal regeneration and degeneration. We examined the role of WND over-expression on sensory neuron morphology by driving WND in multiple subtypes of Drosophila photoreceptors. WND overexpression under control of the pan-retinal GAL4 driver GMR causes multiple photoreceptor defects including cell death, rhabdomere degeneration, and axonal sprouting. Individual photoreceptor subtypes were assayed using GAL4 drivers specific for each photoreceptor class. Many R7 and R8 cells exhibit axonal sprouting while some show cell degeneration. Delaying the onset of WND overexpression until 20 days of age showed that older adult R7 cells retain the ability to initiate new axon growth. R1-6 photoreceptor cells degenerate in response to WND expression and exhibit rhodopsin loss and rhabdomere degeneration. RNAi knockdown of the MAPK signaling components KAY and HEP attenuates the WND-induced loss of Rh1 rhodopsin. UAS-induced HEP expression is similar to WND expression, causing degeneration in R1-6 photoreceptors and axonal sprouting in R7 photoreceptors. These results demonstrate that WND in adult Drosophila photoreceptor cells acts through MAPK signaling activity with both regenerative and degenerative responses. These photoreceptors provide a tractable experimental model to reveal cellular mechanisms driving contradictory WND signaling responses.